A (partial) replication study of Hjort and Poulsen (2019) - Marc Sangnier (Institute for Replication (I4R), 2023)
Hjort and Poulsen (2019) examine how fast Internet affects employment in Africa. Their difference-in-differences estimates exploit differences in the time at which locations were connected to the network of fast Internet cables. The authors find that fast Internet increases employment rates and that this effect is driven by high-skilled occupations. Authors show that, if anything, employment inequality falls when fast Internet becomes available. This study uses replication materials made available with the original article. It first attempts to reproduce results of the original paper from available replication materials. Most results are reproducible, but some are not. Second, this study presents a sensitivity analysis that tests how reported results vary depending on whether a specific country (or region) is excluded from the sample. The paper's results are found to be differently sensitive to the composition of the sample of observations. This analysis also helps to uncover that some specifications that use a large number of fixed effects might actually be too demanding for reasonable identification to be achieved from the data.
Keywords: 330